Synthesis and Characterization of Some Transition Metal Complexes of Dithiocarbamate Ligand Derived from p-Toluidine - Tarique, Mohammad; Aslam, Mohammad (Asian Journal of Chemistry, 2010)
Transition metal complexes with dithiocarbamate ligand derived from p-toluidine and selected metal ions of 3d-series have been synthesized and characterized by elemental analyses, conductivity measurements and Fourier transform infrared spectroscopic technique. All the complexes were found to be non-ionic in nature. The bidentate behaviour of the dithiocarbamate ligand has been confirmed on the basis of the physico-chemical studies.